International Students’ Cultural and Social Experiences in a British University: “Such a hard life [it] is here” - Newsome, Linda K.; Cooper, Paul (Journal of International Students, 2016)
The authors in this qualitative study examined international students’ cultural and social experiences using data collected through case studies and semi-structured, in-depth, informant style interviews. Participants were all international students (n=18), mostly postgraduate from Asian and Far Eastern countries studying at a British higher education institution. The students’ personal journeys are traced through a three-stage process that moves from (1) high initial expectations, through (2) culture shock, to (3) various eventual patterns of accommodation. In addition to capturing the sometimes raw personal experiences of individuals, the study also delineates the ways in which geopolitical and social-emotional factors coalesce to shape students’ personal experience and self-concepts.